(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Background. It is noticeable that doctors’ avoidant behavior while dealing with emotional consequences of critical events not only lowers physician’s quality of sleep (Kahn, Sheppes, & Sadeh, 2013), brings them less satisfaction with the results of their work (Gleichgerrcht & Decety, 2013), but also worsens medical care as they provide poorer services related to the patient (Austin Saylor, & Finley, 2017; Meier, Back, & Morrison, 2001). The lack of scientifc publications shows that this topic is underresearched and relevant. The purpose of the study is to reveal physicians’ experience of critical events. Methods. Five practicing physicians of anesthesiology-reanimatology and surgery participated in the qualitative part of the research. The data was collected using semi-structured interview and processed using inductive thematic Braun & Clarke (2006) analysis. Results. Qualitative analysis revealed the complicated experiences in a physician’s workplace, which doctors described as: taking responsibilities in the presence of a patient’s death, the risk of burnout and negative emotions experienced after a critical event. The analysis also emerged techniques used in dealing with emotions after critical events and consequences of the latter in one’s personal life. Conclusions. The study revealed that physicians in their work environment come across difculties such as risk of burnout, balancing between formal and informal communication with patients and emotional strain which is caused by facing a patient’s death. Doctors tend to cope with negative emotions that emerge during critical events using various methods, but the most elucidated technique was the avoidance to deal with emotions. Analysis also revealed that experiences, gained through medics’ work, modify their attitude towards life and death and change the emotional connection between a physician and his relatives. Keywords: critical incident, death, medical mistake, avoiding emotions, medic.